2014
DOI: 10.9790/2402-08713743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two eco-friendly insecticides (Dennettia tripetala & Piper guineense) against Dermestes maculatus (Degeer) on smoked dried Clarias gariepinus (Pisces: Clariidae)

Abstract: The efficacy of pulverized and extracts of Dennettia tripetala and Piper gunieense indigenous to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There is increase in area of contact between the particles and insect cuticle because there is greater surface volume ratio in smaller particles (Korunic 1998; Nwaubani et al, 2014;Otitodun et al, 2015). al., 2014;Otitodunet al, 2015) and BLA (Dwivedi et al, 2006;Mohapatra et al, 2011;Olawale, 2020), which kills the insects by absorption of the epicuticular wax of the insect, leading to desiccation and death (Subramanyam and Roesli, 2000;Athanassiou and Steenberg, 2007). Table 1 of this study reveals that all the test dusts were observed to have potentials of reducing adult emergence.…”
Section: Resultsmentioning
confidence: 98%
“…There is increase in area of contact between the particles and insect cuticle because there is greater surface volume ratio in smaller particles (Korunic 1998; Nwaubani et al, 2014;Otitodun et al, 2015). al., 2014;Otitodunet al, 2015) and BLA (Dwivedi et al, 2006;Mohapatra et al, 2011;Olawale, 2020), which kills the insects by absorption of the epicuticular wax of the insect, leading to desiccation and death (Subramanyam and Roesli, 2000;Athanassiou and Steenberg, 2007). Table 1 of this study reveals that all the test dusts were observed to have potentials of reducing adult emergence.…”
Section: Resultsmentioning
confidence: 98%
“…The efficacy of the ethyl acetate and n-Haxane could be attributed to their oily appearance, in contrast to the solid methanolic extracts, which is similar to the finding of Ajayi and Peter (2016) who reported extract of P. guineense yielded oil which has been reported to be very effective in the control of stored product pest. The use of plant extract and other forms of plant materials as insect pest control and management of stored food products have been reported by several researchers (Fasakin, 2003;Adebote et al, 2006;Akinwumi et al, 2007;Olayinka, 2014;Fasakin, 2003) and it has been shown that oil extracts obtained from P. guineense, Monodora myristica, and African melegueta were highly effective in controlling various stages of D. maculatus on smoked fish during storage. The oil extracts of these plants were 100% effective when compared with 16.7% in untreated (control) smoked fish.…”
Section: Discussionmentioning
confidence: 99%
“…Botanical pesticide tends to have broad spectrum activity relatively specific in their mode of action and easy to process and use (Viglianco et al, 2008). To minimize use of synthetic pesticide, several plants' extracts have been reported as effective against D. maculatus on dried fish by several researchers (Fasakin, 2003;Akinwumi et al, 2006Akinwumi et al, , 2007Akpotu and Adebote, 2013;Olayinka, 2014). These extracts provide a solution to the problem emanating from the use of synthetic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Their powders were sieved through a mesh size of 1mm 2 and stored separately in tight lid containers at 28 ± 3°C and 75 ± 5% RH (relative humidity). Acetone extract of the botanicals was obtained separately using a cold extraction method [40]. This was done by soaking 300g of the powder in an extraction bottle containing 900ml of acetone for 72 hours.…”
Section: Methodsmentioning
confidence: 99%